The Dynamics of Religiosity among Members of Muslim Minority in Purbo Jolotigo Talun of Pekalongan Central Java - Esti Zaduqisti; Ali Mashuri; Purnomo Rozak (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
The study aimed to describe the dynamics of religious awareness experience, religious maturity, religious conversion, and factors that influence religiosity among Muslim minorities in Purbo, Pekalongan, Central Java, Indonesia. it employed a qualitative descriptive research method within which the informants were selected using snowball sampling. The results showed that firstly, the religious awareness of the Muslim minorities in Purbo reflects an expression of feelings that they are called to believe in Islam, and it is a gift from Allah SWT. Meanwhile, the religious experience reflects ritual worship that is considered as a religious demand. Secondly, the religious maturity of them has not fully fulfilled its criteria as theorized. It has unique characteristics. Thirdly, there are two types of religious conversions, are: converting to Islam and leaving from Islam. Fourthly, factors that influence the dynamics of Muslim minority in Purbo are age of development and experience of subjective diversity, education, environment, and culture.